Alteration of Endocrine Hormones and Antibody Responses in Different Spectrum of Tuberculosis Disease - Tsegaye, Yosef; Admassu, Wasihun; Edao, Abebe; Kinde, Samuel; Gentu, Meaza; Negash, Markos; Wondmagegn, Tadelo; Gize, Addisu; Zewdie, Martha; Bobosha, Kidist; Wassie, Liya (Frontiers in Immunology, 2022)
Effective control of Mycobacterium tuberculosis (Mtb) infection is mediated by multifaceted factors that involve both the endocrine and immune system. Profiling hormones and antibodies in different stages of TB provides insight in the pathogenesis of the disease. In this study, we profiled endocrine hormones (dehydroepiandrosterone (DHEA), cortisol, testosterone, estradiol, growth hormone and leptins) and Mtb strain H37RV lipoarabinomannan (LAM)-specific antibody levels in plasma samples, collected from pulmonary TB (PTB) patients, TB lymphadenitis (TBLN) patients and latently infected (QFT-positive) or uninfected (QFT-negative) apparently healthy individuals using ELISA. Plasma levels of leptin and DHEA were significantly low in PTB and TBLN patients compared to healthy controls (P<0.0001 and P=0.02, respectively), whereas these levels significantly increased following anti-TB treatment (P=0.002 and P=0.0001, respectively) among TB patients. The levels of estradiol and testosterone significantly improved following anti-TB treatment (P=0.03 and P=0.0003, respectively), whereas cortisol and growth hormones declined significantly (P <0.05). Similarly, LAM-specific IgG, IgM and IgA were significantly higher in PTB patients compared to other groups, whereas levels of IgG1 subtype were significantly higher among LTBI groups compared to both TB patients and QFT-negative individuals (P<0.0001). Overall, we observed significantly variable levels of endocrine hormones as well as immunoglobulins across the spectrum of TB illness and such profiling has a significant contribution in selection of effective biomarkers that have roles in TB treatment monitoring or diagnostics. Although this study did not show a functional association between hormones and antibodies, alterations in the levels of these biomarkers suggest the key roles these markers play in TB pathogenesis.